1964
DOI: 10.1113/jphysiol.1964.sp007407
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of skeletal muscle blood vessels (rat cremaster)

Abstract: The recent description of the rat's cremaster muscle by Majno, Palade & Schoefl (1961) suggested that this muscle might provide a suitable site for direct observation of skeletal muscle blood vessels in the living animal. This proved to be so and the method developed allows the study of the reactions of the vessels to various stimuli applied topically and intravenously. It is thought that the vessels are seen in a state that, for a time at least, is nearly normal for resting skeletal muscle. The only comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 21 publications
2
52
2
1
Order By: Relevance
“…The autonomic control of vasomotor functions could be involved in the muscles metabolism (Grant, 1966;Baez, 1973;Fleming et al, 1987Fleming et al, , 1989Franken et al, 1996;Berg et al, 1997;Kurjiaka, 2004). In fact, during the contraction of a muscle it is possible to observe a local functional vasodilatation, quickly followed by a sympathetic vasoconstriction (Thomas and Segal, 2004).…”
Section: Vacht-immunoreactivitymentioning
confidence: 99%
“…The autonomic control of vasomotor functions could be involved in the muscles metabolism (Grant, 1966;Baez, 1973;Fleming et al, 1987Fleming et al, , 1989Franken et al, 1996;Berg et al, 1997;Kurjiaka, 2004). In fact, during the contraction of a muscle it is possible to observe a local functional vasodilatation, quickly followed by a sympathetic vasoconstriction (Thomas and Segal, 2004).…”
Section: Vacht-immunoreactivitymentioning
confidence: 99%
“…In the male rat the GFn has been variously reported to arise from lumbar spinal nerves 2 and 3 (Greene, 1955;Clegg & Doyle, 1966;Grant, 1966), and lumbar spinal nerves 1 and 2 (Hodson, 1970;Hebel & Stromberg, 1986), confirmed more recently by the use of immunohistochemical techniques (Nagy & Senba, 1985;Wang et al 1989; Kar et al 1990). Running caudally, the lumbar spinal nerves converge to form the GFn proper.…”
Section: Introductionmentioning
confidence: 90%
“…The femoral branch has been reported to innervate the inguinal skin in the rat (Greene, 1955;Clegg & Doyle, 1966;Hebel & Stromberg, 1986) and humans (Hollinshead & Rosse, 1985;Reid & Cros, 1999) and the scrotal skin in the rat (Clegg & Doyle, 1966), and the genital branch also to innervate the scrotal skin in the rat (Greene, 1955;Clegg & Doyle, 1966;Nagy & Senba, 1985;Hebel & Stromberg, 1986) and humans (Reid & Cros, 1999), the cremaster muscle (Cm) surrounding the testes in the rat (Greene, 1955;Clegg & Doyle, 1966;Grant, 1966;Adams et al 1967;Hebel & Stromberg, 1986) and humans (Hollinshead & Rosse, 1985;Reid & Cros, 1999), the spermatic cord and vaginal tunica of the testes in the rat (Durwood, 1964;Miller et al 1964), and the dartos muscle lining the scrotal sac in humans (Mitchel, 1938;Clegg & Doyle, 1966). However, more recently it has been reported in the rat that the scrotum is innervated by branches of the pudendal nerve (Pacheco et al 1997;McKenna & Nadelhaft, 1986) and not by the GFn.…”
Section: Introductionmentioning
confidence: 99%
“…Grant (1) and Majno et al (2) proposed that the vasculature of the rat cremaster muscle is an appropriate model for the purpose of observing microcirculation in the striated muscle in vivo. The histological structure of the rat cremaster muscle is similar to one of the skeletal muscles of the extremeties, and the vas culature of the cremaster is innervated by the sympathetic nerve (1,3). By removing only the fascia of the cremaster muscle, the microcirculation can be easily observed without complicated manipulations.…”
mentioning
confidence: 84%
“…administration of these two drugs, arteriolar vasoconstriction was observed. Grant (1) showed that adrenaline given i.v. caused arterial dilatation of the rat cremaster though this sympathomimetic constricted the artery when applied topically .…”
Section: Discussionmentioning
confidence: 99%